History of Pakistani Cricket Team: Challenges and Response ,1947-1970 - Chunying, Ma; Ahmad, Maqbool (Annals of Human and Social Sciences, 2023)
Cricket as the most popular game of the world has its own history. This sport faces different challenges and evolves as a tremendous sport. It started with the passion of Elite classes and eventually came to the streets. In India, game of cricket has a colonial background. After partition, Pakistani cricket had to face certain challenges as the lack of resources, the organizational skills and team spirit, cricket team survived through thick and thin. Pakistan always had wonderful players in bowling and batting. This paper is an attempt to trace the history of Pakistani cricket team which represents its country in marvelous way and creates history in all fields. From the idea of western cricket, Pakistani cricket introduced many indigenous styles of bowling and batting. But it is a fact that Pakistan was always in search of western coaches for the training of its team. The argument of this paper deals with the idea that talent is beyond the boundaries and challenges and response of Pakistani Cricket team always had best players who made their mark in the history of cricket. Pakistan cricket face ed a lot of issues but survive. In the historical idea of challenge and response make Pakistani cricket team, a best team of all times. Both primary and secondary sources are used to prove the argument in this paper. Descriptive and historical method is used to analyze the main idea.